The Presence technology system of textile production worker in pandemic context with hybrid model TAM-AHP - Hendi Iskandar; Dian Noor Hayati; Rikzan Bachrul Ulum; Darmawan Yudhanegara (Jurnal Teknologika, 2021)
Production activities in the context of a pandemic are hampered by the spread of the corona virus, while the company's business must continue to run. The company that is being studied in this research is a textile company in the production sector. The results of this study were carried out by selecting the type of technology according to the company's conditions heuristically. The available technology variants in the market can be various types of technology, the more innovative and cheaper they are, but not all of them get optimal results according to the required conditions. The method used is hybrid model are technology acceptance model and analytical hierachy process. The results of the research obtained that the technology system needed is composed of several criteria, namely the detection of employees every arrival, data early detection of body temperature that can reject or accept employees into the production room, technology that is in accordance with the health and comfort of production employees in ergonomic standards, has a low price according to the company budget, and maintenance technology is easier to use with scoring 0,4050. All of these criteria are based on company needs according to field conditions and company policies in consistency ratio on value 0,0625.